'Less a New African Music than an African New Music'1: A Close Musical Analysis of Bongani Ndodana-Breen's Emhlabeni. Issue 1 (2nd January 2018) - Brukman, Jeffrey
Abstract : Premiered in February 2013, Emhlabeni (In this world) a sinfonia concertante for piano and orchestra by South African composer Bongani Ndodana-Breen, highlights the significance of African art music as a tool for understanding and appreciating the differences and similarities between diverse cultures and their music traditions. Situated in the long-established performance medium of Western art music (solo piano with traditional symphony orchestra), Emhlabeni also embraces thematic material derived from South Africa's African choral tradition and compositional processes drawn from traditional African musicking. Here, African-styled interlocking figures, mbira patterning, pentatonic scales, uhadi chord progressions, and passages that treat the piano like an African mallet percussion instrument are interwoven with elements reminiscent of African jazz (especially Abdullah Ibrahim's trademark tremolandi ). Hence, Ndodana-Breen's musical language is located largely in the African musical–cultural experience, although it is performed through a Western medium and formulated within the parameters of a Western genre: it represents the essence of African art music. Inspired by a popular African choral work, Bawo Thixo Somandla ('Father God Almighty'), Ndodana-Breen chose a title that refers to a subsidiary theme in Bawo that contains the text ' Emhlaben' sibuthwel' ubunzima ' ('On this earth we bear many hardships'). An inspiring composition for those oppressed during apartheid—especially those suffering under the yoke of the brutal Ciskei homeland government, who were mere puppets in the hands of the apartheid regime— Bawo speaks of hope rather than defeatism, although it also reflects on the heavy burdens carried by ordinary citizens. This article emphasizes the artistic dialogue that transpires as Ndodana-Breen appropriates African and Western influences; the article draws attention to Emhlabeni 's political and social significance, especially the irony of a once-'inferior' choral work standing alongside the dominant Western art music tradition, and it provides commentary on the value of African art-music practice in a multicultural society.